2018
DOI: 10.1093/jmammal/gyy102
|View full text |Cite
|
Sign up to set email alerts
|

Breeding seasonality in the lowland paca (Cuniculus paca) in Amazonia: interactions with rainfall, fruiting, and sustainable hunting

Abstract: The resilience of a given species to hunting is conditioned by the effect of potential threats upon the more sensitive periods in its life history, such as when animals are breeding. We investigated the environmental drivers of breeding seasonality in the lowland paca (Cuniculus paca), and the potential impact of hunting on the species. As part of a participative study with hunters in 2 Amazonian sites, we obtained reproductive organs of pacas as well as information on the hunters’ daily wild meat extraction. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 47 publications
0
32
0
1
Order By: Relevance
“…Model results for the red brocket deer, collared peccary, and agouti also showed seasonal visitation, even though these species are known to breed year‐round (El Bizri et al., 2018; Mayor et al., 2011). Several other studies have described increased visitation at mineral licks before reproduction for other species, including Amazonian bats (Bravo et al., 2008; Voigt et al., 2008), white‐tailed deer (Atwood & Weeks, 2002, 2003), and African elephants (Holdø et al., 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Model results for the red brocket deer, collared peccary, and agouti also showed seasonal visitation, even though these species are known to breed year‐round (El Bizri et al., 2018; Mayor et al., 2011). Several other studies have described increased visitation at mineral licks before reproduction for other species, including Amazonian bats (Bravo et al., 2008; Voigt et al., 2008), white‐tailed deer (Atwood & Weeks, 2002, 2003), and African elephants (Holdø et al., 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Both species are declining in central Amazonia (Parry & Peres 2015). Other highly cited species, such as lowland paca, are also affected by hunting in Amazonia (e.g., Valsecchi et al 2014;El Bizri et al 2018), but are listed as least concern by IUCN.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, even when there is consideration of the findings in the present study that pacas sexually mature earlier than what was previously reported, pacas still reproduce less efficiently than expected when calculations were based on data from previous studies. In addition, pacas produce one offspring per gestation and in Amazonia there is an unexpected seasonal pattern of reproduction that converges with periods when there is greater hunting intensity and consequently the harvesting of a large number of pregnant females for human consumption (Oliveira et al, 2007;Mayor et al, 2013Mayor et al, , 2017Valsecchi et al, 2014;El Bizri et al, 2018). When results of the present and previous studies are considered, there needs to be a critical review of previous population sustainability assessments for the species, and calculations of sustainable yields for future in situ management actions (ie., establishment of hunting quotas) should be more conservative.…”
Section: Assessmentsmentioning
confidence: 99%
“…Additionally, the paca is a uniparous species with rare cases of twin gestations (Pérez and Hernández, 1979;Merrit, 1989;Oliveira et al, 2003Oliveira et al, , 2007. In the Amazon, the lowland paca in its natural habitat has 1.37-1.48 annual parturitions that are seasonally distributed depending on the amounts of fruitification and river water, with a long estimated farrowing interval of 247-266 days (Mayor et al, 2013;El Bizri et al, 2018).…”
Section: Introductionmentioning
confidence: 99%